Penggunaan Model Cooperative Learning Tipe Numbered Heads Together (NHT) Untuk Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran Ilmu Pengetahuan Sosial (IPS) (Kelas IV SD Negeri 050779 Serang Jaya Kabupaten Langkat T.A 2015/2016) - Tukiman Tukiman (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2017)
IPS is one of the subjects contained in the curriculum in Elementary School (SD). However, from the learning outcomes in IPS class IV Elementary School 050779 Serang Jaya Langkat District, is still very far from the expected. This is because students do not like IPS lessons. Therefore, the Cooperative Learning model of Numbered Heads Together is used to improve student learning outcomes in IPS learning. The method used in this research is PTK (Classroom Action Research). The results obtained are IPS Learning on Cooperative material in the Indonesian Economy through the implementation of Cooperative Learning model type Numbered Heads Together can improve student learning outcomes and the ability of student cooperation at the time of IPS learning in the elementary school class N0. 050779 Serang Jaya Langkat Regency using cooperative learning model type Numbered Heads Together well developed.